2020
DOI: 10.1002/ccr3.2580
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax with high‐dose methotrexate and rituximab seem effective and well‐tolerated in the treatment of central nervous system involvement of chronic lymphocytic leukemia: A case report

Abstract: Venetoclax with high‐dose methotrexate and rituximab seem effective and safe to treat central nervous system involvement of chronic lymphocytic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The HER2-FASN lipogenic axis therefore delineates a subgroup of patients that might benefit from therapeutic regimens containing FASNis and BCL-2 BH3 mimetics. The recent discovery that brain metastases in HER2 + breast cancer patients rely on FASN [82,83] illuminates the important translational impact of combining blood-brain-barrier penetrable versions of FASNis and BCL-2 BH3 mimetics such as venetoclax, which has already shown a potential efficacy in the treatment of malignancies with central nervous system involvement [84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…The HER2-FASN lipogenic axis therefore delineates a subgroup of patients that might benefit from therapeutic regimens containing FASNis and BCL-2 BH3 mimetics. The recent discovery that brain metastases in HER2 + breast cancer patients rely on FASN [82,83] illuminates the important translational impact of combining blood-brain-barrier penetrable versions of FASNis and BCL-2 BH3 mimetics such as venetoclax, which has already shown a potential efficacy in the treatment of malignancies with central nervous system involvement [84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there have been two reports showing the effectiveness of venetoclax against CNS lesions ( Table 2 ). 17 , 18 One of those was a case where venetoclax was effective after Ibr resistance, and thus it may be beneficial to test venetoclax against CNS involvement in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported in case reports in patients with AML and CLL. Reda et al and Beziat et al in patients with CLL [13,14,17]. Reda et al was first to report venetoclax concentrations close to the IC50 of CLL cells in the CSF of a CLL patient (1.…”
Section: Discussionmentioning
confidence: 99%
“…5 -2.8 ng/ml) receiving 400 mg of venetoclax [13]. Moreover, Beziat et al demonstrated that administering venetoclax in combination with systemic chemotherapy was tolerated and resulted in well-controlled CNS manifestations in another CLL patient with minimal side effects [17]. In fact, neurologic improvements were maintained under continuous venetoclax exposure, six months after the last methotrexate infusion, with absence of new symptoms [17].…”
Section: Discussionmentioning
confidence: 99%